506PEfficacy and safety of pegvorhyaluronidase alfa (PEGPH20; PVHA) and pembrolizumab (pembro) combination therapy in patients (Pts) with stage III/IV non-small cell lung cancer (NSCLC). (24th November 2019) - Ward, J P; Shum, M; Bertino, E; Lin, V; Kuruvadi, V; Heineman, T
Abstract: Background: Immunotherapy is a promising treatment option for advanced NSCLC; however, its efficacy may be limited by accumulation of hyaluronan (HA). PEGPH20 degrades tumor-associated HA and increases the efficacy of chemo- and immuno-therapeutic agents in animal models. Here we report efficacy and safety results of PEGPH20 plus pembro in a cohort of pts with Stage IIIB/IV NSCLC in the 2-cohort, phase Ib dose escalation (DE) and expansion (DX) HALO 107-101 study (NCT02563548). Methods: This analysis included pts with advanced NSCLC and ≥1 prior platinum-based chemotherapy (DE: 1.6 µg/kg and 2.2 µg/kg of PEGPH20, 2 pts per dose) and pts with HA-high NSCLC (HA staining ≥25% of tumor surface), previously untreated or treated with 1 prior platinum-based chemotherapy (DX: 17 pts). PEGPH20 was given on days 1, 8, and 15 and pembro (DE = 2 mg/kg; DX = 200 mg) on day 1 of 21day cycles. Pts received enteric-coated aspirin (81 mg daily) for thromboembolism prophylaxis. Primary endpoints included: DE: doselimiting toxicity, recommended phase 2 dose (RP2D); DX: objective response rate (ORR). Secondary endpoints included: ORR (DE only), disease control rate (DCR), progression-free survival (PFS), overall survival (OS), and safety. Results: Mean pt age was 68 years; 76% of pts had an ECOG PS 1, and 52% were women. The RP2D dose of PEGPH20 was 2.2 μg/kg. A total of 17 of 21 enrolled pts had evaluable tumor responses: 4 had a partial response, 8 had stable disease, and 5 had progressive disease. ORR was 24% and DCR 71%. PFS rates at 6, 12, and 18 months were 25%, 0%, and 0%, respectively, and OS rates were 62%, 47%, and 31%, respectively. Any-grade treatment-emergent adverse events (TEAEs) were reported in all pts, the most common events being muscle spasms (71%), myalgia (43%), nausea (38%), fatigue (29%), and peripheral edema (29%). Grade ≥3 TEAEs were reported in 57% of pts; 38% of pts experienced ≥1 serious adverse event (AE). There was 1 (5%) treatment-emergent thromboembolic AE. Conclusions: The combination of PEGPH20 with pembro has an acceptable safety profile that is consistent with results from other PEGPH20 clinical trials and demonstrates activity in pts with locally advanced or metastatic NSCLC. Clinical trial identification: NCT02563548. Editorial acknowledgement: Medical writing support provided by Miriam Cohen, PhD, of Paragon Medica, Knutsford, UK, supported by Halozyme Therapeutics Inc. Legal entity responsible for the study: Halozyme Therapeutics Inc. Funding: Halozyme Therapeutics Inc. Disclosure: E. Bertino: Advisory / Consultancy, Speaker Bureau / Expert testimony: Pfizer; Advisory / Consultancy: Takeda. V. Lin: Shareholder / Stockholder / Stock options, Full / Part-time employment: Halozyme Therapeutics Inc. V. Kuruvadi: Full / Part-time employment: Halozyme Therapeutics Inc. T. Heineman: Leadership role, Shareholder / Stockholder / Stock options: Halozyme Therapeutics Inc. All other authors have declared no conflicts of interest.